Study on learning mobility - Kirdulytė, Greta,Abozeid, Omar,Makauskė, Giedrė,Del Cogliano, Debora,Pupinis, Mantas,Schouenborg, Jacob,Fras, Max,Ponchon, Carole,Nicodemi, Susie,Dumcius, Rimantas (Publications Office of the European Union, 2023)
European policies and programmes have been promoting and structuring learning mobility across the Union for decades. Despite the progress in creating learning mobility opportunities for a wider and more diverse group of participants, learners and staff members face obstacles to learning mobility. The study identified lack of financial means, awareness about the existing opportunities, unified recognition policies and practices and even lack of interest as the main obstacles to learning mobility across different education and training sectors, youth and sport. In order to mitigate the existing obstacles to learning mobility, the study made recommendations to increase the budget allocations for national and European learning mobility programmes, increase awareness about learning mobility opportunities for different target groups, improve the recognition practices of qualifications and learning periods abroad, lower the administrative burden related to learning mobility applications, and enhance inclusiveness of learning mobility opportunities. In order to better assess the progress of learning mobility in Europe, data collection and monitoring practices should also be strengthened. Using a variety of research methods, this report strengthened the evidence base and supported the work in preparing a Commission proposal for a Council Recommendation on learning mobility to mitigate the existing barriers using various research methods.
10.2766/504434
Keywords: Graue Literatur; Amtliche Publikation; EU-Bildungspolitik; Bildungswesen; Mobilität; EU-Staaten; EU policy; education policy; student mobility; learning; vocational training; vocational education; statistical method; research method; data processing; cartography; young person; adult education; higher education; distance learning; budget policy; professional qualifications; digital literacy; report